THE FUTURE OF BUREAUCRATIC REFORM IN COMBATING CORRUPTION: INTEGRATING GOOD GOVERNANCE AND THE INDONESIAN LEGAL SYSTEM - Wibowo, Chyntia Deby; Wanandi, Caura Candigia Sahid; Azzikrah, Wan Nafisatin Neha (LPPM Univ. Ibn Khaldun Bogor, 2026)
This research discusses the urgency of bureaucratic reform as a key strategy in combating corruption in Indonesia, emphasizing the integration of Good Governance principles and the national legal system. Bureaucratic reform is seen as a fundamental step to enhance transparency, accountability, and the effectiveness of equitable public services. The objective of this study is to identify both challenges and opportunities in building a clean bureaucracy through strengthening legal norms and the continuous application of good governance practices. This research method employs a qualitative approach with literature analysis from regulations, previous studies, and related institutional documents. Research results show that the success of bureaucratic reform is highly determined by the consistency of applying Good Governance principles that align with the Indonesian legal system, especially in the aspects of law enforcement, internal oversight, and inclusive public participation. These findings emphasize that Indonesia's future in combating corruption heavily relies on the synergy between transparent bureaucracy, strong rule of law, and community involvement in the ongoing democratic process.